Transformation Prospect of Inclusive Elementary School Non-Disaster Preparedness Schools in Implementing Management of Child Safety Education - Widowati, Evi; Sugiharto, Sugiharto; Wahyuningsih, Anik Setyo; Husodo, Adi Heru; Istiono, Wahyudi (Unnes Journal of Public Health)
Children is a person aged 0 to 18 years old, including fetus. Primary School X is an inclusive primary school that enrolls children with special needs, located in a disaster-prone area and never been exposed to information and training related to child safety education. The purpose of this study is to investigate the readiness of Primary School X as Inclusive Primary School Non-Disaster Preparedness Schools in implementing child safety education management in schools. This study combines descriptive and analytic studies. Descriptive study was used to assess school management condition through 28 assessment and was conducted through interviews, document study and observation. The analytic study used was quasi-experimental study with one group pre- and post-test design. The result showed that the readiness level of Primary School X to transform into multi-disaster-based child safety was 36%, which is included into transformation ?ready? category.